Karakterisasi Morfologi dan Uji Senyawa Kimia Jamur Makroskopis di Logging Over Area (Area Bekas Penebangan) Taman Hutan Raya Sultan Syarif Hasyim - Liska Chairani Harahap; Tetty Marta Linda; Nery Sofianti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to determine the types and detect the content of secondary metabolites of macroscopic fungi that are predominantly found in the Sultan Syarif Hasyim Forest Park. The method used in this study was an exploratory method in logged-over areas. The macroscopic fungi found were identified, and the dominant fungi were tested for chemical compounds such as alkaloids, flavonoids, tannins, terpenoids, steroids, and saponins. The morphological characteristics observed were referenced in identification books, applications such as Mushroom Identifier, and websites: champignouf.com and inaturalist.org. Based on the results of the identification of macroscopic fungi in the Sultan Syarif Hasyim Grand Forest Park in Riau Province, there are 10 families with 18 types of macroscopic fungi, namely Fomes fomentarius, Lentinus sp., Microporus affinis, Microporus xanthopus, Pycnoporus sanguineus, Trametes pubescens, Trametes ochracea, Trametes villosa, Auricularia mesenterica, Crepidotus sp., Baeospora myosura, Ganoderma lobatum, Galerina sp., Gymnopilus sp., Fomes fomentarius, Mycena galericulata, Oudemansiella furfuracea, Nigroporus vinosus, Suillus bovinus, and chemical compound testing was conducted on 6 types of fungi, namely Fomes fomentarius, Microporus xanthopus, Microporus affinis, Pycnoporus sanguineus, Ganoderma lobatum, and Trametes ochracea. All dominant fungal species showed positive saponin results. Fomes fomentarius and Ganoderma lobatum showed positive terpenoid results. In conclusion, this study found macroscopic fungi that have potential as medicine. Keywords: Basidiomycota, Exploration, Macroscopic fungi, Sultan Syarif Hasyim Forest Park, and Chemical Compound Testing